Effects of combined plyometric and speed training on change of direction, linear speed, and repeated sprint ability in young soccer players a pilot study - Kargarfard, Mehdi; Tajvand, Shadi; Rabbani, Alireza; Clemente, Filipe Manuel; Jalilvand, Farzad (2020)
It has been well established that plyometric and speed training have positive impacts on fitness parameters in soccer players. The aim of this study was to compare short-term effects of a combined plyometric and speed training implemented on the same or separate days of a week on change of direction (COD), linear speed (LS), and repeated sprint ability (RSA) in young soccer players. Twenty-four male players from the same U19 soccer team were distributed into one control group (CG; n=7, soccer training only) and two experimental groups performing plyometric and speed exercises on the same (CDG; n=8) or separate days (CWG; n=9) during a 6-week preparation period. Very likely moderate within-group COD improvements were observed in the CDG (ES -0.94 [-1.47 to -0.41]) and CWG (ES -0.97 [-1.52 to -0.42]) groups. Possibly small within-group RSA improvements were also observed in the CWG (ES -0.24[-0.64 to 0.16]) and CDG (ES -0.31 [-0.79 to 0.17]) groups. CWG and CDG groups showed possibly small (ES -0.28 [-0.62 to 0.06]) and very likely moderate (ES -0.80 [-1.28 to -0.32]) within-group LS improvements following the intervention, respectively. In between group analysis, a likely moderate (ES 0.71 [0.03 to 1.39]) greater LS improvement was observed in the CDG group than in the CWG group. It is suggested to supplement normal soccer training with combined plyometric and speed exercises to improve COD, LS, and RSA performance and to implement these exercises in the same session to improve LS with a greater effect.
Bibliografija: str. 91-93.
Summary.
Keywords: Nogometaši -- Mladi -- Trening -- Agilnost